Expanded In-School Instructional Time and the Advancement of Health Equity: A Community Guide Systematic Review. Issue 6 (November 2019) - Peng, Yinan; Finnie, Ramona K. C.; Hahn, Robert A.; Truman, Benedict I.; Johnson, Robert L.; Fielding, Jonathan E.; Muntaner, Carles; Fullilove, Mindy T.; Zhang, Xinzhi
Abstract : Expanded in-school instructional time (EISIT) may reduce racial/ethnic educational achievement gaps, leading to improved employment, and decreased social and health risks. When targeted to low-income and racial/ethnic minority populations, EISIT may thus promote health equity. Community Guide systematic review methods were used to search for qualified studies (through February 2015, 11 included studies) and summarize evidence of the effectiveness of EISIT on educational outcomes. Compared with schools with no time change, schools with expanded days improved students' test scores by a median of 0.05 standard deviation units (range, 0.0-0.25). Two studies found that schools with expanded day and year improved students' standardized test scores (0.04 and 0.15 standard deviation units). Remaining studies were inconclusive. Given the small effect sizes and a lack of information about the use of added time, there is insufficient evidence to determine the effectiveness of EISIT on academic achievement and thus health equity. Abstract : Supplemental Digital Content is Available in the Text.